Is It Mum or the Dad? Parental Factors That Influence the Use and Acceptance of Fluoride Varnish among Parents in Eastern Saudi Arabia. (13th December 2022) - Aljami, Abdullah; Alshehri, Turki; Altuwaijri, Abdulrahman; Aldossary, Alhanoof; Almutairi, Wejdan; Farooqi, Faraz Ahmed; Gaffar, Balgis
Abstract : Objective . To investigate parental factors that influence knowledge, use, and acceptance of fluoride varnish (FLV) application. Methods . This cross-sectional study was conducted during December 2021. A multistage sampling technique was used to recruit parents with children aged 3 to 6 years and residing in Eastern Saudi Arabia, excluding those working in the dental field. The questionnaire consisted of four parts: demographics, knowledge, previous experience, and acceptance of FLV and was pilot-tested and distributed online using social media. Results . A total of 623 parents responded to the survey. Only 36.9% of parents had good FLV knowledge with dentists being the main source of information. Gender, educational level, family income, being in the medical field, and source of knowledge were factors that significantly (P < 0.05 ) influenced parental knowledge. Only 24.6% of the parents applied fluoride varnish to their children before, of whom only 29% were satisfied with the experience. Parent's FLV knowledge, view of dental visits, satisfaction with previous experience, perception of children's oral health, and willingness to reapply FLV were factors that significantly (P < 0.05 ) influenced FLV use. Working in the medical field, perception of dental visits, and the source of knowledge were factors that significantly (P < 0.05 ) influenced the parent's acceptance to apply FLV. While lack of knowledge about fluoride benefits (15%) was the main reason for parental refusal to apply FLV. Conclusions . The current study highlights the lack of knowledge and application of FLV among parents. There were more factors influencing mothers' acceptance of FLV application compared to fathers. Age, educational level, working in the medical field, perception, and patterns of dental visits were some of the identified factors. Dentists played a major role in parental knowledge and FLV acceptance. In a country with high caries prevalence, preventive programs such as FLV education and application are crucial.